The effect of mediating role of organizational resilience on human resource management and continuity of performance in the general directorate of residency and foreigners affairs Dubai - Albannai, Mana Mohammad Ahmad Mohammad (2024)
Performance continuity was essential for the General Directorate of Residency and Foreigners Affairs (GDRFA) in Dubai, necessitating the integration of Human Resource Management (HRM) practices and organizational resilience strategies. This study highlighted how HRM policies enhanced the organization's adaptability and resilience, ensuring long-term success and sustained performance. The GDRFA of Dubai has experienced challenges in maintaining performance continuity due to its static and conventional training approaches, which failed to incorporate new trends in employee development, thereby hampering the organization's ability to adapt to rapidly changing conditions and ensure long-term success. Although advanced training programs have been introduced, however it has not been widely adopted across all departments, resulting in inconsistent implementation and benefits. Hence, the objective of this study was to investigate the effect of HRM on performance continuity within the GDRFA of Dubai. The study further investigated the mediating effect of organizational resilience between HRM and performance continuity. This quantitative research employs a cross-sectional design using a questionnaire as the research instrument. The researcher distributed 540 questionnaires to the respondents, out of which 364 questionnaires were found usable for analysis. The data was analysed using Analysis of Moment Structures- Structural Equation Modelling (AMOS-SEM). Fifteen hypotheses were formulated and tested. The results supported nine hypothesised relationships, which were significant and positive. Specifically, the findings imply that chain of command, delegation span of control and organizational resilience had a substantial influence on the continuity of performance. The study found that the mediating effect of organizational resilience does not significantly mediate the relationship between work specialization and authority with performance continuity, while it does significantly mediate the relationships with chain of command, delegation, and span of control. Theoretically, this study contributed to the use of Resource-Based View (RBV) Theory in studying the context of HRM and organizational resilience in enhancing the performance continuity of GDRFA of Dubai. From a practical point of view, this study found that adopting flexible HRM strategies and enhancing organizational resilience are important strategies that can be considered by the government, regulatory authorities, councils and the management of the GDRFA of Dubai for future performance continuity.